Ichthyofauna of the river Halda, Chittagong, Bangladesh - Azadi, Mohammad Ali; Alam, Mohammad Arshad Ul (Bangladesh Journal of Zoology, 2015)
Eighty-three species of finfish belonging to 13 Orders, 35 Families, and 69 genera including three exotic species, and 10 species of shellfish (crustaceans) under one order, 3 families and 3 genera were identified from the River Halda during September 2004 to December 2011. Thus a total of 93 species of Ichthyofauna (finfish and shellfish) were recorded from this river during the seven years (2004-2011) of investigation. Maximum number of finfish species were recorded under the family Cyprinidae (19 species) followed by the family Gobiidae (11 species), whereas maximum number of shellfish species were recorded under the family Palaemonidae (8 species) followed by Penaeidae (1 species) and Portunidae (1 species). Of the 83 finfish species, three belonged to the critically endangered, nine to the endangered and eight to the vulnerable category according IUCN (2000). Four species of finfish were new records from inland waters of Bangladesh. A systematic list of the ichthyofauna with local and English names, and habitat preference are provided. Bangladesh J. Zool. 41(2): 113-133, 2013